(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article clarifies the structure and history of the architectural monument of Sultan Mir Haydar which was located in the Kasbi district of the Kashkadarya region, including the life path and names of His Highness Sultan Mir Haydar.